Lycium ningxiaense, a replacement name for Lycium parvifolium T.Y. Chen & Xu L. Jiang (Solanaceae) - Liao, Qi; Wang, Ruijiang (Phytotaxa, 2014)
The genus Lycium Linnaeus (1753: 191) is one of the largest genera in Solanaceae Jussieu (1789: 124), with approximately 92 species in the monogeneric tribe Lycieae Hunziker (1977: 28; Levin et al. 2011). It is disjunctly distributed in temperate to subtropical regions between the northern and southern hemispheres, mainly in North America, South America, southern Africa, and Eurasia (Zhang et al. 1994, Fukuda et al. 2001). It is characterized by spiny shrubs and small trees, fasciculate leaves, campanulate calyx, and by fleshy and juicy berry. Traditionally Lycium berry has been used medicinally worldwide.